Desenvolvimento de um Sistema de Informação Médica com WebServices e MDA - MELO, Simone Azevedo Bandeira de (2007)
In this work, we develop a medical information system to support medical diagnosis based on an approach oriented to models, in which the system allows sharing of information between physically scattered specialists. The development of a medical information system is done using MDA (Model Drive Architecture) in which the PIM (Platform Independent Model) is created with UML (Unified Modeling Language), and the PSMs (Platform Specific Model) is done according to Web Services Platforms. To implement this system, we devised meta model s for the Web Services, JWSDP (Java Web Services Developement Pack) and WSOracle. Thus, we provide definitions of transformation of UML for the Web Services, JWSDP and WSOracle. The development of the system puts in evidence the process of transformation of PIM for PSM used in MDA.